Painful Ophthalmoplegia of Right Eye in 40-Year-Old Female - Diagnosed As A Case of Tolosa-Hunt Syndrome (Journal of Dhaka Medical College, 2016)
Tolosa-Hunt Syndrome (THS) is a painful opthalmoplegia caused by nonspecific inflammation of cavernous sinus or superior orbital fissure. Here, we present a case of THS who presented with severe unilateral headache and opthalmoplegia, responded dramatically with systemic steroidJ Dhaka Medical College, Vol. 24, No.2, October, 2015, Page 160-162